Power Subsystem Design Of The Malaysian Youth Satellite (Mysat) - Subramaniam, Sasidaran (Universiti Sains Malaysia, 2018)
MYSat (Malaysian Youth Satellite) is a nanosatellite that is being developed by the Universiti Sains Malaysia Space Lab team. Its purpose falls under the scope of earthquake forecasting in which functions to sense and transmit electron density data using special equipment during its one year orbit at Earth’s ionospheric altitude. This final year project focuses on the design and implementation of electronic power subsystem (EPS) of MYSat.The main task of EPS is to provide a continuous supply of power to the entire satellite bus in orbit without failure. The power system consists of several main parts: Solar cells, batteries, power distribution bus which consists of voltage converters and protection, sensors monitoring different parts of the system and a microcontroller or an on-board computer used to control the system. The output of this project is a simplest yet feasible EPS model on a breadboard and to test its capability to ensure successful power delivery to all payload and will be fabricated as an Engineering model in the form of the printed circuit board (PCB) before its integration into the MYSat mainframe. The procedure of this project is to size every stage of the EPS by considering the architecture, power budget, type of power management and regulations, switching methods and trade-off between different hardware that are reliable and available in the market. Initially, this system is made to be an independent system for the testing purpose. Each critical component was tested individually followed by the combined circuit form to investigate the power output. The system is then has incorporated a standalone microcontroller unit that functions to provide fault protection and displays necessary voltage and current data at particular parts of the system. The control system will be switched to MYSat On-Board data handling subsystem later on.